One step excision combined with unilateral transforaminal intervertebral fusion via minimally invasive technique in the surgical treatment of spinal dumbbell-shaped tumors: A retrospective study with a minimum of 5 years’ follow-up - Pan, Jianfeng; Gu, Yutong; Zhang, Feng (Frontiers in Surgery, 2022)
Introduction. Spinal dumbbell-shaped tumors are rare, usually benign tumors with intraspinal and paravertebral components by connected through intervertebral foramen. Complete excision is often performed through traditional open surgery (TOS). The efficacy and long-term outcomes of minimally invasive surgery (MIS) have not been reported to date in resections of dumbbell-shaped spinal tumors. Purpose. The purpose was to evaluate the efficacy and long-term outcomes of minimally invasive resection combined with unilateral transforaminal intervertebral fusion (TIF) through comparing with TOS in the treatment of spinal dumbbell-shaped tumors. Methods. Fifteen patients underwent MIS and eighteen patients were performed through TOS. Thoracic dumbbell-shaped tumors were directly exposed after removal of costotransverse joints, adjacent rib components, unilateral hemilamina and facet joints. Lumbar dumbbell-shaped tumors were completely exposed after removal of transverse processes, unilateral hemilamina and facet joints. Whether for minimally invasive resection or traditional open removal, dumbbell-shaped tumors were completely excised and unilateral TIF was performed to guarantee spinal stability. All patients were followed up for 5 years at least. Results. The mean length of surgical incision for two groups was 3.47±0.37 cm vs 6.49±0.39 cm (p<0.05). The average duration of the operation was 131.67±26.90 minutes vs 144.17±23.59 minutes (p>0.05). The mean blood loss was 172.00±48.79 mL vs 285.83±99.31 mL (p<0.05). No blood transfusions were required in the two groups. The median length of hospitalization was 6 days vs 10 days. (range: 5-8 days vs 7-14 days). The patients of two groups were followed up for an average of 65.93±3.88 months vs 65.78±3.56 months. At 5-year follow-up all patients were presented with normal neurological function (ASIA scale E). ODI in MIS group decreased significantly more than TOS group. No spondylolisthesis and spinal instability were found in the period of follow-up. There was no recurrence of any spinal tumor 5 years after surgery. Conclusions. Spinal dumbbell-shaped tumors can be safely and effectively treated with minimally invasive resection combined with unilateral TIF. Compared with TOS, MIS offers a reduced length of surgical incision, blood loss, hospital stay, and postoperative pain. This surgical protocol might provide an alternative for the treatment of spinal dumbbell-shaped tumors.